Micro surfacing with latex modified emulsion (FHWA-OK-86-7) 2416 - (:unkn) unknown (My University, 1986)
This is the final report for the use of emulsified asphalt in a relatively new process called "Ralumac Micro Surfacing". This process was developed in Germany and was first used in the United States in late 1980. In 1982, personnel from the Oklahoma Department of Transportation (ODOT) Observed projects in another state and proposed a project in Oklahoma. The Ralumac process incorporates natural latex rubber with the aspha;tt emulsion. It is mixed with aggregate and other additives in a traveling pug mill similar to but larger than that of a regular slurry machine. The construction phase of this demonstration project was completed in June, 1983. The evaluation of data presented shows that the service life of the test area has been enhanced. It is recommended the Ralumac process be approved for routine use as a restoration item for flexible pavements to fill surface ruts and cracks, seal the surface, and restore skid resistance.
Keywords: Seal coats; Micro surfacing; Rut filling